Faktor-Faktor yang Mempengaruhi Fenomena Audit Delay di Bursa Efek Indonesia - Adhika Wijasari, Luh Komang; Ary Wirajaya, I Gde (E-Jurnal Akuntansi; Vol 31 No 1 (2021)DO - 10.24843/EJA.2021.v31.i01.p13, 2021)
Audited financial reports are considered a reliable source of information for users of financial information in order to make decisions, therefore they must pay attention to the factors that affect audit delay. This study aims to determine the effect of auditor switching, financial distress, KAP reputation, and the Covid-19 pandemic on audit delay. The study was carried out at the Indonesian Stock Exchange's mining firms for the period 2017-2019. The number of samples in this study were 105 companies using nonprobability sampling techniques. Multiple linear regression analysis is selected as the technique in analyzing the data. Based on the analysis, it is known that auditor switching has no effect on audit delay, financial distress has a positive effect on audit delay, and the reputation of KAP has a negative effect on audit delay. There is a significant difference in the audit delay before the Covid-19 pandemic and during the Covid-19 pandemic. Keywords: Audit Delay; Auditor Switching; Financial Distress; Reputation of KAP; Pandemic Covid-19.